2016
DOI: 10.1111/jonm.12452
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transformational leadership of nurse managers

Abstract: The results of this study emphasise the need for emotional intelligence continuing education, leadership development and leader assessment programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The study results for emotional intelligence are consistent with the findings of studies in head nurses and managers of various organisations in the USA. It revealed that emotional intelligence positively and significantly correlated with the level of transformational leadership.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study results for emotional intelligence are consistent with the findings of studies in head nurses and managers of various organisations in the USA. It revealed that emotional intelligence positively and significantly correlated with the level of transformational leadership.…”
Section: Discussionsupporting
confidence: 88%
“…Part 2 was leadership assessment. The Multifactor Leadership Questionnaire version (MLQ) 5× short (http://www.mindgarden.com) was used as a tool to assess leadership in this study because it is one of the most widely used instruments to measure leadership in many countries and in a number of organisations including those of health professionals. In addition, it has been developed and used for over two decades, and has acceptable validity and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that only age, professional qualification and working experience have contribution for job satisfaction as p-value < 0.05. A study conducted by Echevarria, Patterson, and Krouse (2017) they found that the bachelor degree nurses satisfaction is higher and it is produced by a conflict for associate degree nurses.…”
Section: Discussionmentioning
confidence: 98%
“…It is the most widely adopted leadership model used (Kirkbride, 2006) and a framework used to develop their knowledge and skills related to leading staff (McGuire & Kennerly, 2006). Transformational leadership includes: charisma or idealized influence; inspirational motivation; intellectual stimulation, and individualized consideration -which tend to be positively associated with 'emotional intelligence (Echevarria, Patterson, & Krouse, 2017). Idealized influence characterizes leaders who are ideal role models for followers (Bass & Riggio, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 99%